Analisis dampak harga emas dunia, harga minyak dunia, kurs, Indeks Harga Konsumen (IHK), dan BI rate terhadap Jakarta Islamic Index - Muhammad Umar Azyka Alfuadi (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2019)
Purpose — The paper attempts to analyze the impacts of the gold price, oil price, exchange rate, consumer price index, and BI rate on the Jakarta Islamic Index.Research method — This study employs VAR-VECM to analyze all secondary data collected. The period is from January 2009 until December 2011.Result — The result shows that in long term all variables have a significant impact on Jakarta Islamic Index. The gold price has a negative impact on Jakarta Islamic Index at 4,1% and is stable after 12 months, the oil price has a positive impact of 1% and stable after 21 months, the exchange rate has a positive impact of 3,8% and stable after 17 months, the consumer price index has positive impact 0,5% and stable after 21 months, and BI rate has negative impact 6,2% and stable after 15 months. BI rate also gives the biggest impact on Jakarta Islamic Index among others.